Analysis Of The Influence Of Sustainability Reporting, Auditor Switching, And Good Corporate Governance On Going Concern Audit Opinion - Annisa Nurbaiti; Emeralda Diva Vania (Publikasi Indonesia, 2023)
Going concern is a basic assumption of financial statements preparation, where the company must able to maintain its operational survival in the present and also be able to continue the business in the future. The purpose of this study is to test the influence of sustainability reporting, auditor switching, and good corporate governance as measured through variables of managerial share ownership, independent commissioners, board of directors, and audit committees on the provision of audit opinions on the going concern of coal sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. This research uses a quantitative method research. This research used logistic regression for data analysis using Eviews 12. The research results show that the variables of sustainability reporting, auditor switching, and good corporate governance measured through managerial share ownership, independent commissioners, board of directors, and audit committee simultaneously affect audit opinions. Furthermore, managerial share ownership variables positively influence the provision of audit opinions going concern. In addition, the independent commissioner variable negatively influences the provision of audit opinions. Meanwhile, the variables of sustainability reporting, switching auditors, board of directors, and audit committees have no partial effect on the provision of audit opinions going concern